2009
DOI: 10.1007/s00415-009-5108-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and clinical relevance of brain atrophy in multiple sclerosis: a review

Abstract: Multiple sclerosis is known to be an inflammatory demyelinating disease characterized mainly by multifocal areas of white matter lesions. Recently, cortical lesions and brain atrophy have emerged as new pathological markers of disease progression. Brain tissue loss can now be easily and reproducibly detected and quantified by MRI, which has led to an increasing amount of research correlating brain tissue loss with other MRI markers, such as white matter lesions, and to clinical disabilities (motor or cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 101 publications
(240 reference statements)
3
51
1
1
Order By: Relevance
“…The latter finding is compatible with the observations that the cerebellum receives major NE projections from the locus coeruleus (26) and that the stress hormone NE is closely linked to inflammatory processes (9,10). Thus, given that inflammation is a source of GM atrophy (38), which is pronounced in the cerebellum (29,39), one might conclude that the negative link of stress-induced brain activity and GM atrophy might be mediated by the NE system. Importantly, analysis 4a also showed that stress-induced activity is positively related to GM volume in overlapping cerebellar areas of controls.…”
Section: Discussionsupporting
confidence: 87%
“…The latter finding is compatible with the observations that the cerebellum receives major NE projections from the locus coeruleus (26) and that the stress hormone NE is closely linked to inflammatory processes (9,10). Thus, given that inflammation is a source of GM atrophy (38), which is pronounced in the cerebellum (29,39), one might conclude that the negative link of stress-induced brain activity and GM atrophy might be mediated by the NE system. Importantly, analysis 4a also showed that stress-induced activity is positively related to GM volume in overlapping cerebellar areas of controls.…”
Section: Discussionsupporting
confidence: 87%
“…1,2 At present, the most commonly used radiologic markers for disease activity and progression are the number of new T2 lesions and gadoliniumenhancing T1 lesions. Brain atrophy is generally afforded a subordinate role in follow-up in clinical practice and is often estimated only by visual inspection.…”
Section: Usefulness and Importance Of This Studymentioning
confidence: 99%
“…Several different techniques based on MR imaging, manual as well as semiautomatic and automatic, can be used to accomplish this. 1,7,8 Manual techniques require postprocessing labor that may limit the feasibility of clinical use and may introduce operator-dependent errors, making automated techniques a preferable alternative. Automated methods generally use image intensity histograms of conventional MR image acquisitions, either to separate tissue types directly by setting intensity thresholds or for comparison with brain templates or a priori tissue maps.…”
mentioning
confidence: 99%
“…Moreover, high contrast makes segmentation between the different cerebral compartments easier. Depending on the compartment of interest, tissue contrast can be chosen such as CSF/parenchyma or gray/white matter (Grassiot et al, 2009). There are many different segmentation methods for estimating brain volume using manual or automated techniques.…”
Section: Methods For Volume Estimationmentioning
confidence: 99%